PENGARUH MEDIA PROMOSI PERBANKAN SYARIAH TERHADAP MINAT MENABUNG MASYARAKAT DI BANK SYARIAH - Ortega, Daniel; Alhifni, Anas (EQUILIBRIUM, 2017)
This study aims to determine the promotion of Islamic banking media that influence in attracting the public interest to save in sharia banks. Promotion media used by sharia banking in this research is divided into 3, namely: newspaper media, television media and internet media. The method used in this research is quantitative descriptive method with multiple linier regression analysis technique. The data used in this study is the primary data in the form of questionnaires distributed to the public. Based on data analysis that has been done, television and internet variables have a greater contribution than the variable newspaper in increasing public interest to save in Bank Syariah.